PENGARUH KEPERCAYAAN DIRI, MOTIVASI BELAJAR, DAN LATAR BELAKANG PENDIDIKAN MENENGAH TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi Kasus pada Mahasiswa Program Studi Akuntansi Universitas Slamet Riyadi Surakarta) - Djoko Kristianto, Putri Andini Indah Lestari, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The purpose of this study is to analyze the influence of self-confidence on the understanding of accounting, learning motivation toward the understanding of accounting, and the background of secondary education to the understanding of accounting, as well as analyzing differences in understanding accounting by gender and background. This study uses case studies on accounting students at Slamet Riyadi University Surakarta. The population in this study are all students of accounting study program at Slamet Riyadi University Surakarta and sample of 76 students by using purposive sampling. Data were collected using questionnaires and data analysis techniques using multiple linear regression analysis and independent sample t-test. The results of the study concluded that: 1) There is a positive and significant influence of confidence on the understanding of accounting at Slamet Riyadi University Surakarta. 2) There is a positive and significant influence of learning motivation towards the understanding of accounting at Slamet Riyadi University Surakarta. 3) There is a positive and significant influence of secondary education background towards the understanding of accounting at Slamet Riyadi University Surakarta. 4) There is no difference in the understanding of accounting between male and female students. 5) There is no difference in the understanding of accounting between high school background and SM background.Keywords: self confidence, learning motivation, secondary education background, understanding of accounting.